Rational design and topochemical synthesis of polymorphs of a polymer - Athiyarath, Vignesh (2023)
Packing a polymer in different ways can give polymorphs of the polymer having different properties. β-Turn forming peptides such as 2-aminoisobutyric acid (Aib)-rich peptides adopt several conformations by varying the dihedral angles. Aiming at this, a β-turn-forming peptide monomer would give different polymorphs and these polymorphs upon topochemical polymerization would yield polymorphs of the polymer, we designed an Aib-rich monomer N3-(Aib)3-NHCH2-C[triple bond, length as m-dash]CH. This monomer crystallizes as two polymorphs and one hydrate. In all forms, the peptide adopts β-turn conformations and arranges in a head-to-tail manner with their azide and alkyne units proximally placed in a ready-to-react alignment. On heating, both the polymorphs undergo topochemical azide-alkyne cycloaddition polymerization. Polymorph I polymerized in a single-crystal-to-single-crystal (SCSC) fashion and the single-crystal X-ray diffraction analysis of the polymer revealed its screw-sense reversing helical structure. Polymorph II maintains its crystallinity during polymerization but gradually becomes amorphous upon storage. The hydrate III undergoes a dehydrative transition to polymorph II. Nanoindentation studies revealed that different polymorphs of the monomer and the corresponding polymers exhibited different mechanical properties, in accordance with their crystal packing. This work demonstrates the promising future of the marriage of polymorphism and topochemistry for obtaining polymorphs of polymers.